Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.893561
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus emblica aqueous extract retards hepatic steatosis and fibrosis in NAFLD mice in association with the reshaping of intestinal microecology

Abstract: Accumulating evidence suggests that dysregulation of the intestinal flora potentially contributes to the occurrence and development of nonalcoholic fatty liver disease (NAFLD). Phyllanthus emblica (PE), an edible and medicinal natural resource, exerts excellent effects on ameliorating NAFLD, but the potential mechanism remains unclear. In the present study, a mouse NAFLD model was established by administering a choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD). The protective effects of the aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators. The abundance of Faecalibaculum is known to be significantly elevated in NAFLD mice, which was consistent with our results ( 56 , 57 ). Positive correlations were also found between Faecalibaculum and most therapeutic indicators.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in this study that Muribaculaceae had wide and negative correlations with therapeutic indicators. The abundance of Faecalibaculum is known to be significantly elevated in NAFLD mice, which was consistent with our results ( 56 , 57 ). Positive correlations were also found between Faecalibaculum and most therapeutic indicators.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that Bacteroides plays an important role in alleviating hepatic lipid accumulation in NAFLD mice. Short-chain fatty acids in the gut help protect the integrity of the intestinal barrier, and some studies have claimed that norank_f_ Muribaculaceae is positively correlated with intestinal short-chain fatty acid levels ( 63 , 64 ). In the present study, camel milk and silymarin upregulated the relative abundance of norank_f_ Muribaculaceae in the intestine of NAFLD mice, and we also found that the relative abundance of norank_f_ Muribaculaceae was negatively correlated with serum TG level and liver TG level in the clustering analysis of bacterial genera and physiological indicators, suggesting that norank_f_ Muribaculaceae may regulate the levels of TG in serum and liver by increasing the content of short-chain fatty acids in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting precipitate was lyophilized and the high-molecular weight fraction of AEPE (termed HWPE) was obtained. In our previous studies, the main chemical ingredients in AEPE were quantified by high-performance liquid chromatography (HPLC) and the content of crude polysaccharides in HWPE was determined by phenol-sulfuric acid method ( Yin et al, 2021 ; Luo et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The AEPE and its fractions samples were prepared using the same batch of dried PE fruit (voucher specimens no. 20201212) as in our previous study (Yin et al, 2021;Luo et al, 2022). Briefly, 2000 g of PE was powdered and immersed in distilled water on a rotary shaker for 24 h at a mass ratio of 1:10 at 37 °C.…”
Section: Preparation Of Test Drugsmentioning
confidence: 99%